Coefficient Estimates for Certain Families of Analytic Functions Associated with Faber Polynomial. (1st February 2023) - Attiya, Adel A.; Albalahi, Abeer M.; Hassan, Taher S.
Abstract : In this paper, we use the Faber polynomial expansion to obtain bounds for the general coefficients a n of bi-univalent functions in the family of analytic functions in the open unit disk. Estimation of the bound value for the initial coefficients of the functions in these classes is also established.